News & Views - ., . (Journal of Engineering Education Transformations, 2010)
News: *Â National Conference on Revamping Teacher Education. *Â National Seminar on impact of globalization on higher education in India: opportunities and challenges. *Â National Seminar on Quality Education: Role of Teacher, Technology & Management. *Â International Conference on Education Informatics (EduMatics-201 0). on 22 May, 2010. organized by Chitkara Institute of Engineering and Technology, Rajpura (Punjab) and Indo-US Collaboration for Engineering Education (IUCEE). *Â The XII International Seminar will be held on broad theme "Globalization of Higher Education" from January 4-5,2011 at New Delhi, India. Views : *Â Quality Management of Technical Education in India. *Â Technical Education and TQM.